2006
DOI: 10.1186/1471-2458-6-172
|View full text |Cite
|
Sign up to set email alerts
|

California Men's Health Study (CMHS): a multiethnic cohort in a managed care setting

Abstract: Background: We established a male, multiethnic cohort primarily to study prostate cancer etiology and secondarily to study the etiologies of other cancer and non-cancer conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 24 publications
0
51
0
1
Order By: Relevance
“…Furthermore, the characteristics of the CMHS cohort was similar to the general male population who participated in a random digit dial survey in California. 29 Therefore, our results are likely generalizable to the broader male population in similar age range.…”
Section: Epidemiologymentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the characteristics of the CMHS cohort was similar to the general male population who participated in a random digit dial survey in California. 29 Therefore, our results are likely generalizable to the broader male population in similar age range.…”
Section: Epidemiologymentioning
confidence: 91%
“…A total of 84,170 men including a nearly 40% minority participation completed the questionnaires and hence joined the cohort. Details of the cohort design and recruitment methods were described previously by Enger et al 29 Between study baseline and December 2007, 14,177 men in the cohort terminated their health plan membership (not including death), resulting in a follow-up rate of 83% by end of 2007.…”
mentioning
confidence: 99%
“…Some studies have reported diabetic men to be screened less often (23,47), whereas others have noted no difference or increased screening in some age groups (22). We examined two interval cohorts within our setting (48,49) and found little evidence of differential PSA screening by diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 84,170 men including a nearly 40% minority participation completed the questionnaires and hence joined the cohort. Details of the cohort design and recruitment methods were described previously by Enger et al (10). The CMHS cohort was similar to the population of health plan members on important characteristics and appeared similar to men who responded to a general health survey in California (California Health Interview Survey) on a variety of important demographic and clinical characteristics (10).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the cohort design and recruitment methods were described previously by Enger et al (10). The CMHS cohort was similar to the population of health plan members on important characteristics and appeared similar to men who responded to a general health survey in California (California Health Interview Survey) on a variety of important demographic and clinical characteristics (10). Between study baseline and December 2006, 11,144 men in the cohort terminated their health plan membership, resulting in a follow-up rate of 87% by end of the 2006.…”
Section: Methodsmentioning
confidence: 99%